2012
DOI: 10.1590/s1516-18462012005000027
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência das estratégias de reparo para os fonemas plosivos, considerando o grau do desvio fonológico

Abstract: OBJETIVO: verificar a ocorrência ou não de estratégias de reparo para os fonemas /b/, /d/, /k/ e /g/ e a relação destas estratégias com a gravidade do desvio fonológico. MÉTODO: selecionados 54 sujeitos com diagnóstico de desvio fonológico que apresentavam estratégias de reparo para as consoantes plosivas /b/, /d/, /k/ e /g/ nas posições de onset inicial e/ou medial, com emprego de 40% em seu sistema fonológico. Os dados foram submetidos à análise estatística por meio do programa Statistical Analysis System, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(11 reference statements)
3
3
0
Order By: Relevance
“…Those data agree with several researches that investigated the use of repair strategies in different levels of phonological disorder severity 5,12,[14][15][16][17][18] . Repair strategies are ways used during the phonological acquisition, typical or atypical acquisition, in order to adapt the phonological system, during its formation, to the target phonological system.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Those data agree with several researches that investigated the use of repair strategies in different levels of phonological disorder severity 5,12,[14][15][16][17][18] . Repair strategies are ways used during the phonological acquisition, typical or atypical acquisition, in order to adapt the phonological system, during its formation, to the target phonological system.…”
Section: Discussionsupporting
confidence: 91%
“…In relation to the plosives, the results obtained in this study demonstrated that this class was impaired, mainly, in cases of severe disorders, as in the phonetic inventory, as in the phonological system. This finding confirms what was observed in a study about the occurrence of repair strategies in plosive phonemes, in the different levels of phonological disorder 18 . The authors observed that as levels medium and medium high, to the high level of contrasts, which correspond to the categories 1, 2, 3 and 4, respectively.…”
supporting
confidence: 92%
“…This statement agrees on the results of this research, where younger children employed several resources to facilitate the use of obstruents. In deviant data, results were similar to those in this study, where for the voiced plosive phoneme /g/, repair strategies such as fricatization 23 were used, and for the voiced fricative phoneme /ʒ/, the affrication strategy 24 was used. In the acquisition of plosives, a study showed the use of desonorization and anteriorization in medial onset 20 .…”
supporting
confidence: 78%
“…About the sonority, the occurrence of correct production for the phoneme /k/ was also higher when compared with the phoneme /g/ in atypical speech data 28,29 . Such ascertainment was also proved with the results obtained in this study.…”
Section: Resultsmentioning
confidence: 85%
“…Such ascertainment was also proved with the results obtained in this study. The acquisition of the phoneme /g/ after the phoneme /k/ was evidenced in studies about phonological acquisition 5,8 and the fact that the voiced feature for the plosives is more marked or more complex, may justify the results obtained in these studies 29 .…”
Section: Resultsmentioning
confidence: 95%